Impact of Tuberculosis upon Patients' Quality of Life Who Undergo Directly Observed Treatment Short Course (DOTS) in AL-Amarah City - Arkan Bahlool Nagi; Saad sabri shamkh (Kufa Journal for Nursing Sciences)
Objective: To find the impact of Tuberculosis disease upon quality of life of patients who undergo Directly Observed Treatment Short Course (DOTS).